High resolution monitoring of valvular interstitial cell driven pathomechanisms in procalcific environment using label-free impedance spectroscopy - Böttner, Julia; Werner, Sarah; Feistner, Lukas; Fischer-Schaepmann, Tina; Neussl, Katherina; Borger, Michael A.; Thiele, Holger; Büttner, Petra; Schlotter, Florian (Frontiers in Cardiovascular Medicine, 2023)
Introduction Fibro-calcific aortic valve disease has high prevalence and is associated with significant mortality. Fibrotic extracellular matrix (ECM) remodeling and calcific mineral deposition change the valvular microarchitecture and deteriorate valvular function. Valvular interstitial cells (VICs) in profibrotic or procalcifying environment are frequently used in vitro models. However, remodeling processes take several days to weeks to develop, even in vitro. Continuous monitoring by real-time impedance spectroscopy (EIS) may reveal new insights into this process. Methods VIC-driven ECM remodeling stimulated by procalcifying (PM) or profibrotic medium (FM) was monitored by label-free EIS. Collagen secretion, matrix mineralization, viability, mitochondrial damage, myofibroblastic gene expression and cytoskeletal alterations were analyzed. Results and Discussion EIS profiles of VICs in control medium (CM) and FM were comparable. PM reproducibly induced a specific, biphasic EIS profile. Phase 1 showed an initial impedance drop, which moderately correlated with decreasing collagen secretion (r = 0.67, p = 0.22), accompanied by mitochondrial membrane hyperpolarization and cell death. Phase 2 EIS signal increase was positively correlated with augmented ECM mineralization (r = 0.97, p = 0.008). VICs in PM decreased myofibroblastic gene expression (p < 0.001) and stress fiber assembly compared to CM. EIS revealed sex-specific differences. Male VICs showed higher proliferation and in PM EIS decrease in phase 1 was significantly pronounced compared to female VICs (male minimum: 7.4 ± 4.2%, female minimum: 26.5 ± 4.4%, p < 0.01). VICs in PM reproduced disease characteristics in vitro remarkably fast with significant impact of donor sex. PM suppressed myofibroblastogenesis and favored ECM mineralization. In summary, EIS represents an efficient, easy-to-use, high-content screening tool enabling patient-specific, subgroup- and temporal resolution.